L’alterità dell’altra. Levinas, il femminile, l’umanità dell’umano - Fulco, Rita (Bollettino Filosofico, 2019)
In Levinas’ thought the feminine otherness assumes different connotations and is shrouded in ambiguity. Initially it is assumed as a paradigm of the otherness, then Levinas in Totality and Infinity, especially in the pages about The Dwelling, which have been rightly criticized, attaches a ‘disfigured’ face and a too intimate and familiar relationship with the other (man) to it. According to Jacques Derrida, the most interesting aspect of the strategy by Levinas, which is put in place to reach the radical ‘deposition’ of the Subject, is the hyperbolic revival of some female stereotypes (welcome, vulnerability, maternity), which are assumed in order to characterize the humanity of the Human as such. The otherness of the other (woman) becomes, therefore, the key to the deconstruction of subjectivity and to the understanding of the Human. Keywords: Emmanuel Levinas, Otherness, Feminine, Gender difference, Politics